(3GdCQLhRI GdhLjRIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS GHf SjfG (B: (3GdMeO ddg GdeYGai GdTGai ShGg dG jTai hdG jYGai UGHQ GdCfaS hGdCQhGM eUhQ GdCLSGe hGdCTHGM s
(3BNQgG (B:s
(3agh OhGA MSf GdEYGfI ai ZSdg GdcdjI hGdeKGfI hGdHGQO GdMdh GdUMjM GdHGdZ ai bhI GdUja OhGA SGHZ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQgG eY CdajI GHf SjfG ai GdWH Qbe (B" 337"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B17 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(9) s
Keywords: (3GdWHs